Variation and its valuation in design-build contract with regard to the public sector of Malaysia - Ismail, Nazaitul Hazira (2022)
Previous studies have shown that using a design-build approach may help keep costs down and avoid or significantly reduce the number of variation orders required. Despite this, there is always the possibility for variation to occur. According to the Auditor-General’s Report 2018, several design-build projects expended an additional 20% of the contract sum due to variations and changes to the original scope of work. As a result, project costs and timelines can easily balloon out of control without adequate management. This study was carried out to identify the leading causes contributing to variations, as well as the method for valuing such variations. It focused specifically on design-build projects undertaken by public sector organisations. A total of 10 projects for building and civil engineering works completed between 2011 and 2021 using PWD Form DB 2010 were selected. The primary data were collected through semi-structured interviews with eight senior engineers and senior quantity surveyors involved in the variation administration of the selected case studies. Subsequently, a document study was undertaken to supplement the data collected during interviews. Findings indicate five causes of variation, with changes in the scope of work by the end user being the most common. These employer-related changes are most likely to occur as a result of ambiguity in the Government’s Requirements. Finding out the main causes of variation might aid contract administrators in initiating proactive measures for future design-build public projects to minimise the negative impact on cost and time. Besides that, this study discovered that four methods for valuing variation were used in the selected case studies. Variation can be valued using either Contract Sum Analysis, Contract Schedule of Rates, a fair valuation, or a daywork basis. The suitability and appropriateness of the method for valuing variation varies depending on the conditions in which the obligations and types of work are to be performed. This study would serve as the best practice recommendations for administering variation work in design-build projects, which differ from the conventional projects that most contract administrators are familiar with.